Christianity and national parks: seeing God in nature-based experiences - Jackson, Sarah (Kansas State University, 2021)
To unveil the multilayered experiences which Christians undergo when engaging in nature-based experiences, this research utilized a multidimensional approach to address and further comprehend the characteristics of these moments. Specifically, this research aimed to understand how Christians experience God within nature-based experiences and further how tenets within the structure and expressions associated with their religious belief system address the overarching phenomena and associated lenses. Through the content of the primary phenomena, the lenses which were of focus include investigations concerning the extrinsic composition of these experiences (i.e., presence or absence of individuals, natural contexts and involved surroundings, and engaged religious expressions (i.e., prayer, worship, and using biblical- or religious-based resources)) and how this brought forth intrinsic outcomes as a result (i.e., descriptions regarding experiencing God and influence in solidifying or transforming the environmental mindset of Christians). As a result, this research was completed in a cumulative manner which involves three ventures which act as independent studies while collectively contributing to an overall, enhanced understanding of the complexity of the experienced phenomena primarily in situ (i.e., in nature as defined by NPS units) and ex situ as well (i.e., potential completion of pro-environmental behaviors). Further, this research involved three distinct research questions to inform the progression of this compound endeavor and they include: 1) “How, if at all, do Christians experience God in national parks during communal or group-based ventures?”, 2) “How, if at all, do Christians experience God in national parks during moments of solitude?”, and 3) “How do Christians experiencing God in national parks describe their environmental mindset?”. Regarding the first question, semi-structured interviews in alignment with a phenomenological framework and qualitative foundation were completed in the research settings of Great Smoky Mountains National Park and Indiana Dunes National Park in summer 2020 to approach this inquiry focused on the influence of experiencing God during social interaction through group-based or communal activities in nature (i.e., defined as an accessible NPS unit). Three sources including 1) individuals partaking in a worship service within an NPS unit (N=15), 2) individuals who voluntarily engaged in an extended, overnight stay through a religious-based retreat within an NPS unit (N=5), and 3) individuals who voluntarily chose to serve as employed personnel who facilitated Christian-based religious offerings (i.e., worship service) within an NPS unit (N=16). With 36 total participants, shared expressions amongst sources provided notable and collective highlights of the focus phenomena within this specific unit of the overall research process (i.e., experiencing God during social interaction within nature-based experiences). Specifically, participants portrayed an overall amplification of experiencing the focus phenomena through a “triangle effect” (Mike). This effect involved the components of social interaction, nature, and God which represented the overall amplification of their experiences within nature (i.e., NPS units) which brought forth both individual and collective moments. When engaging in group-based or communal activities, participants relayed the impact of the present “triangle effect” (Mike) and further the foundational role of experiencing God that formed an enhanced level of authenticity in their ventures, such as through in-depth and raw connections with both present individuals, their natural surroundings, and God as well. Overall, participants reflected an increased probability to spend time in nature with others as a result of these formative moments to not only foster meaningful relationships with others and nature, but observe God in varied, renewed exposures as a result of the infiltrating “triangle effect” (Mike). Concerning the second question, the implementation of an additional lens in informing the overarching phenomena of focus in consideration of employing an alternate approach to understand the specifics of experiencing God in nature-based experiences by Christians was used. The involved research settings and implemented interviews involving three sources were maintained as the used methods in reference to all three research questions. In further recognition of the second inquiry including the role of solitude within the ventures of those who identified as Christians, participants conveyed the ability to engage in solitude through both the presence and absence of individuals. While solitude was associated with executing aloneness, participants shared that solitude could occur when in a collective context due to the provision of opportunities to retreat from the group-based moments. Further, participants highlighted the notable role of solitude to provide pause in their nature-based experiences. It is through the pause of solitude and electing to engage in this brief or momentary halt of occurrences which compose a world-based context where participants were able to experience God through opportunities to acquire a renewed or revived perspective concerning their surroundings (i.e., natural and present individuals in a group-based venture), their position within life, their purpose in life, and further their relationship with God. It is through solitude and the involved pause where participants portrayed the progression of transcendental, influential, and pivotal experiences with God in His creation that could serve as filters through which to shift their overall state and reinforce their perceived self-reliance and self-efficacy and through their identification in God to further apply the gathered rejuvenation in all life-based situations (i.e., difficult inhibiting occurrences ranging to climatic or peak experiences). In consideration of the third question, this inquiry provides an all-encompassing investigation regarding the environmental mindset Christians maintain in consideration of their experiencing of God and specifically within nature-based moments. This question aimed to unveil varying influences and roles within the overarching, identified environmental mindset of Christians by describing how natural (i.e., surrounding natural context involving an NPS unit), religious (i.e., expressions including worship, prayer, and using biblical- or religious-based resources), and environmental focuses (i.e., viewpoint of the environment and associated in situ and ex situ behaviors) informed the environmental mindset of participants. Based on this compound approach involving a range of varied focuses to address the complex nature of the applicable phenomena, participants shared a unified reflection of an overarching environmental mindset which is undergirded by their relationship with God. Further, this relationship progressed the formation of an ingrained desire to act in a manner which is reflective of stewardship as directed by the character of God and His biblical-based mandates (i.e., Holy Bible). With this overall baseline, the conveyed environmental mindset of participants was also conveyed by highlighting a varied set of focuses including social, environmental, and religious. Participants expressed their overall environmental mindset as one that places significance on the existence of environmental justice issues and the need for amplifying humanitarian efforts, enhancing pro-environmental and environmentally conscious behaviors and continuously evolving perspectives, and applying this overarching mindset in a manner which ultimately conveys respect for God’s creation and His primary role as the Creator of existence. As a result, participants displayed their environmental mindset as one that is diverse in its composition, but mainly desires to express gratitude to God through conscious behaviors which recognize Him through the furthering of an in-depth relationship and applying this meaningful intrinsic “fabric” within the interactions they have with both nature and individuals as well.
Keywords: Religion; Christianity; Nature; Solitude; Social interaction; Environmental mindset